Europa's far ultraviolet oxygen aurora from a comprehensive set of HST observations. Issue 3 (15th March 2016) - Roth, Lorenz; Saur, Joachim; Retherford, Kurt D.; Strobel, Darrell F.; Feldman, Paul D.; McGrath, Melissa A.; Spencer, John R.; Blöcker, Aljona; Ivchenko, Nickolay
Abstract: We analyze a large set of far ultraviolet oxygen aurora images of Europa's atmosphere taken by Hubble's Space Telescope Imaging Spectrograph (HST/STIS) in 1999 and on 19 occasions between 2012 and 2015. We find that both brightness and aurora morphology undergo systematic variations correlated to the periodically changing plasma environment. The time variable morphology seems to be strongly affected by Europa's interaction with the magnetospheric plasma. The brightest emissions are often found in the polar region where the ambient Jovian magnetic field line is normal to Europa's disk. Near the equator, where bright spots are found at Io, Europa's aurora is faint suggesting a general difference in how the plasma interaction shapes the aurora at Io and Europa. The dusk side is consistently brighter than the dawnside with only few exceptions, which cannot be readily explained by obvious plasma physical or known atmospheric effects. Brightness ratios of the near‐surface OI] 1356 Å to OI 1304 Å emissions between 1.5 and 2.8 with a mean ratio of 2.0 are measured, confirming that Europa's bound atmosphere is dominated by O2 . The 1356/1304 ratio decreases with increasing altitude in agreement with a more extended atomic O corona, but O2 prevails at least up to altitudes of ∼900 km. Differing 1356/1304 line ratios on the plasma upstream and downstream hemispheres are explained by a differing O mixing ratio in the near‐surface O2 atmosphere of ∼5% (upstream) and ≲ 1% (downstream), respectively. During several eclipse observations, the aurora does not reveal any signs of systematic changes compared to the sunlit images suggesting no or only weak influence of sunlight on the aurora and an optically thin atmosphere. Key Points: Analysis of a large set of FUV aurora images of Europa's atmosphere Europa's oxygen aurora is strongly influenced by the plasma environment New constraints on oxygen abundances in Europa's atmosphere